Effect of a quality improvement intervention with daily round checklists, goal setting, and clinician prompting on mortality of critically ill patients: A randomized clinical trial - Cavalcanti, Alexandre B.; Bozza, Fernando Augusto; Machado, Flavia R.; Salluh, Jorge I.F.; Campagnucci, Valquiria Pelisser; Vendramim, Patricia; Guimaraes, Helio Penna; Normilio-Silva, Karina; Damiani, Lucas Petri; Romano, Edson; Carrara, Fernanda; de Souza, Juliana Lubarino Diniz; et al. (American Medical Association (AMA), 2016)
IMPORTANCE: The effectiveness of checklists, daily goal assessments, and clinician prompts as quality improvement interventions in intensive care units (ICUs) is uncertain. OBJECTIVE: To determine whether a multifaceted quality improvement intervention reduces the mortality of critically ill adults. DESIGN, SETTING, AND PARTICIPANTS: This study had 2 phases. Phase 1 was an observational study to assess baseline data on work climate, care processes, and clinical outcomes, conducted between August 2013 and March 2014 in 118 Brazilian ICUs. Phase 2 was a cluster randomized trial conducted between April and November 2014 with the same ICUs. The first 60 admissions of longer than 48 hours per ICU were enrolled in each phase. INTERVENTIONS: Intensive care units were randomized to a quality improvement intervention, including a daily checklist and goal setting during multidisciplinary rounds with follow-up clinician promptingfor 11 care processes, or to routine care. MAIN OUTCOMES AND MEASURES: In-hospital mortality truncated at 60 days (primary outcome) was analyzed using a random-effects logistic regression model, adjusted for patients' severity and the ICU's baseline standardized mortality ratio. Exploratory secondary outcomes included adherence to care processes, safety climate, and clinical events. RESULTS: A total of 6877 patients (mean age, 59.7 years; 3218 [46.8%] women) were enrolled in the baseline (observational) phase and 6761 (mean age, 59.6 years; 3098 [45.8%] women) in the randomized phase, with 3327 patients enrolled in ICUs (n = 59) assigned to the intervention group and 3434 patients in ICUs (n = 59) assigned to routine care. There was no significant difference in in-hospital mortality between the intervention group and the usual care group, with 1096 deaths (32.9%) and 1196 deaths (34.8%), respectively (odds ratio, 1.02; 95% CI, 0.82-1.26; P =.88). Among 20 prespecified secondary outcomes not adjusted for multiple comparisons, 6 were significantly improved in the intervention group (use of low tidal volumes, avoidance of heavy sedation, use of central venous catheters, use of urinary catheters, perception of team work, and perception of patient safety climate), whereas there were no significant differences between the intervention group and the control group for 14 outcomes (ICU mortality, central line-associated bloodstream infection, ventilator-associated pneumonia, urinary tract infection, mean ventilator-free days, mean ICU length of stay, mean hospital length of stay, bed elevation to ≥30°, venous thromboembolism prophylaxis, diet administration, job satisfaction, stress reduction, perception of management, and perception of working conditions). CONCLUSIONS AND RELEVANCE: Among critically ill patients treated in ICUs in Brazil, implementation of a multifaceted quality improvement intervention with daily checklists, goal setting, and clinician prompting did not reduce in-hospital mortality.